Penerapan Strategi Pembelajaran Langsung dalam Membentuk Kompetensi Berpikir Kritis Peserta Didik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore the application of direct instruction strategies in shaping students' critical thinking competence. This strategy focuses on a clearly structured learning process that enables students to gradually understand and apply learning concepts. The success of this strategy's implementation heavily relies on several supporting factors, such as the quality of questions posed by the teacher, effective classroom management, and active student involvement. Furthermore, the direct instruction strategy has a significant impact on classroom practices, particularly in enhancing the quality of interactions between teachers and students and strengthening students' critical thinking skills. This research employs a qualitative research method with a literature review approach, examining various relevant literature on the topic. The findings suggest that the application of this strategy can improve students' critical thinking abilities, which are essential to prepare them for the challenges of the 21st-century life.